A photogenic bronze on square: Carlos Gomes by João Turin (TEL Tempo, Espaço e Linguagem, 2021)
This article is about the meanings that permeate the invention of pedagogical memories and political narratives in the photographic reproductions of the bust of Carlos Gomes, made photogenically by João Turin. It takes support on visual sources to study the appropriations of sculptural language by the technical image, as well as the theoretical-methodological thoughts of Crary, Henisch and Miceli.